La gestión administrativa de la cooperativa de ahorro y crédito sol de los Andes y su incidencia en el otorgamiento de créditos de consumo en la ciudad de Riobamba en el año 2014. - Duran Pilamunga, Fernanda Gabriela (2017)
This research was conducted in order to determine whether the administrative management of the credit union Sol de los Andes and its impact on lending for consumption in the city of Riobamba in 2014. Cooperatives are businesses that are intended to improve and properly maximize the living conditions of its members. Their intention is to meet its economic, social and cultural needs. They have been one of the most important for the advancement of heritage in society as these have had a favorable growth and well received by the public by the facilities offered by other financial institutions pieces. Every company or cooperative must be assessed both internally and externally in order to know their weaknesses on which we must take preventive and corrective measures, to discover whether its resources and activities are designed under the concept of efficiency, effectiveness and economy, and if management is aimed at achieving the institutional mission, for which it requires the continued support of the members of the Cooperative considering they are the engine of the institution. The first chapter is disclosed by the reference frame the problem to be studied in the research, objectives, justification and importance of it. Second chapter consists of theoretical and conceptual framework that enabled expand knowledge of the problem under study and influence of each of the variables. Third Chapter: the methodological framework, type of research, research design, techniques and research tools, sample and data processing was determined. In the fourth chapter the conclusions and recommendations found in the research are developed. Finally in the fifth and final chapter discloses the literature that I use to support this research.